Rethinking Disability: The Emergence of New Definitions, Concepts and Communities - Devlieger, Patrick; Rusch, Frank R.; Pfeiffer, David 1934- (Antwerp Garant, 2003)
This book provides an interdisciplinary approach to the challenges of the interface between disability & culture. Twelve papers discuss the following topics: Towards a cultural model of disability. Disability Values, Representations & Realities. Labeling in the Name of Equality: Political & Social Realities in the Schooling of Disabled Students. Understanding Disabilities-the Emergence of Our Understanding of Sameness. Can Disability Be Thought of in Terms of Difference? The Disability Studies Paradigm. Examining the Fit Between Deafness & Disability. Winks, Blinks, Squints & Twitches-Looking for Disability & Culture Through My Son's Left Eye. The Common Agenda of Aging & Disabilities-Stalemate or Progress. From "Idiot" to "Person with Mental Retardation"-Defining Difference in an Effort to Dissolve It. Virtual Support Groups-An Ethnographic Interpretation.Patrick Devlieger is Assistant Professor at the University of Illinois' Department of Disability, as well as Associate Professor at the Department of Social & Cultural Anthropology, University of Leuven (Belgium).
Keywords: Remedial education